IMPLEMENTASI PROGRAM USAHA EKONOMI KELURAHAN-SIMPAN PINJAM HARAPAN BERSAMA - Septian, Andrico; Rusli, Zaili; R.F.S, Harapan Tua (Jurnal Ilmu Administrasi Negara, 2019)
Implementation of the Economic Business Program of the Savings and LoansHarapan Bersama Village. This research is a qualitative type. The research informant was thechairperson of UEK-SP and his staff Lurah, Chair of LPM and Women Leaders. Data collectiontechniques are interviews, observation and documentation. Data analysts use interactive modelsranging from data presentation, data reduction and conclusion drawing. The results of this studyindicate that the implementation of UEK-SP in Kampung Melayu Village has not fully touched thecommunity, the high arrears of loans by the community, namely the lack of awareness of thepublic to pay its debts, and the lack of optimal guidance and supervision activities.